End-stage kidney diseases in immigrant groups: a nationwide cohort study in Sweden - Wändell, Per (Am J Nephrol, 2019)
BACKGROUND: Our aim was to study the association between country of birth and incident end-stage kidney disease (ESKD) in several immigrant groups in Sweden, using individuals born in Sweden or with Swedish-born parents as referents. METHODS: A cohort study of first- and second-generation immigrants residing in Sweden between January 1, 1998 and December 31, 2012 was performed. Outcomes were defined as having at least one registered diagnosis of ESKD in the National Patient Register. The incidence of ESKD in different immigrant groups, was used in the Cox regression models to estimate hazard ratios (HRs) and 95% confidence intervals (CI). All models were stratified by sex and adjusted for age, geographical residence, educational level, marital status, and neighbourhood socioeconomic status. RESULTS: Compared to their referents, higher incidence rates and HRs of ESKD (HR; 95%CI) was observed in general among foreign-born men (1.10; 1.04–1.16) and women (1.12; 1.04–1.21) but not among second-generation immigrants (persons born in Sweden with foreign-born parents). A particularly high incidence was noted among men and women from East-European countries, as well as from non-European regions. A lower incidence of ESKD was noted among men from Finland. CONCLUSIONS: We observed substantial differences in incidence of ESKD between immigrant groups and the Swedish-born population, which may be clinically relevant when monitoring preventive measures in patient subgroups with a higher risk of deteriorating kidney disease, and suggest higher attention to hypertension and diabetes control in immigrants. Mechanisms attributable to the migration process or ethnic differences may lead to an increased risk of ESKD.